How prepared is Fiji to climate and geopolitical risks? Insights from a socio-metabolic risk (SMR) analysis - Bhargav Singh Thakur; Simron Jit Singh; Michael O. Wood (Journal of Industrial Ecology, 2026)
Small Island Developing States (SIDS) contribute little to global emissions yet face disproportionate climate and market shocks. Their vulnerability is geographic and structural, driven by external resource dependence, lock-in of hazard-zone stocks, and weak circularity. The Socio-Metabolic Risk (SMR) concept addresses these drivers by linking material flows and stocks to systemic fragility. This study provides the first operationalization of SMR through a longitudinal (2000–2022) economy-wide material flow analysis (ew-MFA) mass-balance account for a SIDS, using Fiji. We interpret ew-MFA indicators as risk diagnostics: Import Dependence Ratios (IDR) capture exposure to supply shocks; Net Additions to Stock (NAS) trace accumulation of long-lived, hazard-prone assets; and circularity rates measure material recovery. Results show that between 2000 and 2022, Fiji’s overall IDR increased from 27 to 46%, with fossil fuels and metal ores remaining entirely imported, non-metallic minerals increasing from about 11% to 39%, and biomass imports expanding from 6 to 16%. NAS grew sharply, especially for construction materials, embedding cement, clinker, and aggregates into coastal infrastructure vulnerable to climate disasters. Circularity remained negligible, with socioeconomic cycling rates near zero across the period. By applying SMR through a two-decade ew-MFA, we move the concept from theory to practice and show how longitudinal metabolism reveals the trajectory of systemic risk. Fiji’s material metabolism exhibits increasing SMR, underscoring the urgency of diversifying resource access, strengthening recycling, and enforcing resilient “build-back-better” standards.

Towards an ecological metaphor for regenerative circular economies - Filippos K. Zisopoulos; Brian D. Fath; Bruno Meirelles de Oliveira; Susana Toboso-Chavero; Hugo D'Assenza-David; Vitor Miranda de Souza; Hao Huang; Şerban Scrieciu; O. Grant Clark; Dominik Noll; Simron Singh; Alexandros Stefanakis; et al. (Ecological Economics, 2025)

Inequities blocking the path to circular economies: A bio-inspired network-based approach for assessing the sustainability of the global trade of waste metals - Filippos K. Zisopoulos; Brian D. Fath; Susana Toboso-Chavero; Hao Huang; Daan Schraven; Benjamin Steuer; Alexandros Stefanakis; O.Grant Clark; Serban Scrieciu; Simron Singh; Dominik Noll; Martin de Jong (Resources, Conservation and Recycling, 2025)

Household energy systems based on biomass: Tracing material flows from source to service in rural Ethiopia - Harald F. Grabher; Karlheinz Erb; Simron Singh; Helmut Haberl (Ecological Economics, 2024)

From vulnerability to viability: A situational analysis of small-scale fisheries in Asia and Africa - Ana Carolina Esteves Dias; Derek Armitage; Prateep Kumar Nayak; Shehu Latunji Akintola; Evans Kwasi Arizi; Ratana Chuenpagdee; Basanta Kumar Das; Sabiha Ahmed Diba; Raktima Ghosh; Moenieba Isaacs; Gazi Md Nurul Islam; Alioune Kane; et al. (Marine Policy, 2023)

The Bahamas at risk: Material stocks, sea‐level rise, and the implications for development - Francisco Martin del Campo; Simron Jit Singh; Tomer Fishman; Adelle Thomas; Michael Drescher (Journal of Industrial Ecology, 2023)
Recent research suggests that over 75% of resources extracted globally now go toward creating, maintaining, or operating material stocks (MS) to provide societal services like housing, transport, education, and health. However, the integrity of current and future built environments, and the capacity of the system to continue providing services, are threatened by extreme events and sea‐level rise (SLR). This is especially significant for the most disaster‐prone countries in the world: Small Island Developing States. In the aftermath of disasters, complex rebuilding efforts require substantial material and economic resources, oftentimes incurring massive debt. Understanding the composition and dynamics of MS and environmental threats is essential for current and future sustainable development. Drawing on open‐source OpenStreetMap (OSM) data, we conducted a spatially explicit material stock analysis (MSA) for The Bahamas for 2021, where we included buildings and transport MS, and SLR exposure scenarios. Total MS was estimated at 76 million tonnes (Mt) or 191 tonnes per capita (t/cap) of which transport comprises 43%. These MS are likely to increase by 36 Mt in the future. Simulations show that under 1‐, 2‐, or 3‐m SLR scenarios, around 4, 6, and 9 Mt of current MS will be exposed, with transport MS at greatest risk, with over 80% of total exposure in each scenario. Our findings highlight the critical role that key MS play in sustainability and resilience, contributing to the emphasis on effective development planning and climate change adaptation strategies, and to the exploration of the use of OSM data for studying these objectives.

Regenerative economics at the service of islands: Assessing the socio-economic metabolism of Samothraki in Greece - Filippos K. Zisopoulos; Dominik Noll; Simron J. Singh; Daan Schraven; Martin de Jong; Brian D. Fath; Sally Goerner; Ken Webster; Dan Fiscus; Robert E. Ulanowicz (Journal of Cleaner Production, 2023)

The challenge of solid waste on Small Islands: proposing a Socio-metabolic Research (SMR) framework - Simron J Singh; Allison Elgie; Dominik Noll; Matthew J Eckelman (Current Opinion in Environmental Sustainability, 2023)

Can a small island nation build resilience? The significance of resource‐use patterns and socio‐metabolic risks in The Bahamas - Francisco Martin del Campo; Simron Jit Singh; Tomer Fishman; Adelle Thomas; Dominik Noll; Michael Drescher (Journal of Industrial Ecology, 2023)
Resource‐use patterns may entail systemic risks and cascade effects, which consequently inhibit the ability to deliver socioeconomic services. Identifying resource‐use patterns exhibiting systemic risks and reshaping their combinations is a potential lever in realizing the transition to a sustainable, resilient, and resource‐secure system. Using an island context to assess the quantity and composition of resource throughput enables a more comprehensive analysis of these risks. This article presents the first mass‐balance account of socio‐metabolic flows for The Bahamas in 2018, to identify socio‐metabolic risks and cascading effects. Socio‐metabolic risks are systemic risks related to critical resource availability, material circulation integrity, and (in)equities in cost and benefit distributions. We utilize the economy‐wide material flow accounting framework to map the material flow patterns across the economy. In 2018, annual direct material input was estimated at 9.4 t/cap/yr, of which 60% were imports. High masses of waste (1.4 t/cap/yr) remained unrecovered due to the lack of recycling. Total domestic extraction (DE) were dominated by non‐metallic minerals with more than 80%, while marine biomass makes up barely 1% of total DE. Due to its linear, undiversified metabolism, and heavy imports dependency, the system is susceptible to socio‐metabolic risks and cascading effects including low levels of self‐sufficiency, high vulnerability to shocks, commodity price fluctuations, threats to sensitive ecosystems, health impacts, and economic losses, among others. A holistic resource management strategy and nature‐based solutions that consider the trade‐offs and synergies between different resource‐use patterns are critical when exploring potential plans for metabolic risk reduction.

Can the Caribbean localize its food system?: Evidence from biomass flow accounting - Shupa Rahman; Simron Singh; Cameron McCordic (Journal of Industrial Ecology, 2022)
Small island economies are highly dependent on food imports. Self‐sufficiency through food localization is therefore often advocated. Can a small Caribbean island nation localize its food system? To answer this question, we conducted socio‐metabolic research on four Caribbean nations: Barbados, Dominica, Grenada, and Jamaica. Derived indicators from a diachronic biomass flow accounting from 1961 to 2019 suggest a declining trend in local food production for all cases. While in Barbados and Jamaica this decline already began in the 1960s, for Dominica and Grenada, this did not start until the late 1970s–1980s. The physical trade balance of biomass is similar across all cases: from net exporters at the start of the study period to net importers as countries developed, albeit at different time periods. By disaggregating biomass flow data to crop level, Barbados and Jamaica indicate a trend that is moving away from food localization, while Dominica and Grenada appear to be modestly moving toward localization in recent years. Given the many resource security challenges small island economies face, this study provides a biophysical perspective to the Caribbean's food security debate and questions the extent to which food localization is possible in a small island context, and whether other strategies are urgently needed.

The sociometabolic transition of a small Greek island: Assessing stock dynamics, resource flows, and material circularity from 1929 to 2019 - Dominik Noll; Christian Lauk; Willi Haas; Simron Jit Singh; Panos Petridis; Dominik Wiedenhofer (Journal of Industrial Ecology, 2022)

Analyzing Socio-Metabolic Vulnerability: Evidence from the Comoros Archipelago - Jean-Baptiste Bahers; Simron Singh; Mathieu Durand (Anthropocene Science, 2022)

Food Security Challenges and Options in the Caribbean: Insights from a Scoping Review - Elham Mohammadi; Simron Jit Singh; Cameron McCordic; Jeremy Pittman (Anthropocene Science, 2022)

The weight of islands: Leveraging Grenada's material stocks to adapt to climate change - Rob Symmes; Tomer Fishman; John N. Telesford; Simron J. Singh; Su‐Yin Tan; Kristen De Kroon (Journal of Industrial Ecology, 2020)
The building stock consumes large amounts of resources for maintenance and expansion which is only exacerbated by disaster events where large‐scale reconstruction must occur quickly. Recent research has shown the potential for application of material stock (MS) accounts for informing disaster risk planning. In this research, we present a methodological approach to analyze the vulnerability of the material stock in buildings to extreme weather events and sea‐level rise (SLR) due to climate change. The main island of Grenada, a Small Island Developing State (SIDS) in the Caribbean region, was used as a case study. A bottom‐up approach based on a geographic information system (GIS) is used to calculate the total MS of aggregate, timber, concrete, and steel in buildings. The total MS in buildings in 2014 was calculated to be 11.9 million tonnes (Mt), which is equivalent to 112 tonnes per capita. Material gross addition to stock (GAS) between 1993 to 2009 was 6.8 Mt and the average value over the time period was 4.0 tonnes per capita per year. In the year following Hurricane Ivan (2004), the per capita GAS for timber increased by 172%, while for other metals, GAS spiked by 103% (compared to average growth rates of 11% and 8%, respectively, between 1993 and 2009). We also ran a future “Ivan‐II” scenario and estimated a hypothetical loss of between 135 and 216 kilotonnes (kt) of timber from the building stock. The potential impact of SLR is also assessed, with an estimated 1.6 Mt of building material stock exposed under a 2‐m scenario. We argue that spatial material stock accounts have an important application in planning for resilience and provide indication of the link between natural disaster recovery and resource use patterns.